2ndhandgame: buy & sell used games mobile application / Izri Idham Ramlan - Ramlan, Izri Idham (2022)
This mobile application is developed to provide platform for gamers who have a lot of unused games or gamers who are interested in games. The increase of the gaming activities caused the unused games to be dumped into the garbage which can affect the environment. This mobile application is made to overcome the issues that some people may have unused games that they have not been playing anymore or interested anymore but throw away would be a waste and also bring negative effects to environment. The purpose of this mobile application is to help the users to find games they are interested in and also to provide a place where people can sell their used games. This mobile application has a push notification features that will notify users if there is the other user sell games. This will keep the users updated so they will not miss their favourite games. Next, this mobile application has location-based features. With this features, users are able to find the seller location for meet up. Even so, the application has some limitations which is only available for Android device and does not have payment gateway process. Besides, Mobile Application Development Life Cycle is used to build this mobile application and the development only covers from the identification phase to the testing phase. The target user is for the gaming community and people who want to buy or sell their game. Next, the user testing results based on System Usability Scale (SUS) is 76. For the future work, this mobile application is hopefully available for both Android and IOS device and provide payment gateway in the mobile application.